2013
DOI: 10.3109/19401736.2013.792075
|View full text |Cite
|
Sign up to set email alerts
|

The phylogenetic placement ofSiniperca obscurabase on complete mitochondrial DNA sequence

Abstract: The extant freshwater sinipercids represent a group of 12 species and they are endemic to East Asia. In this study, we cloned and sequenced the complete mitochondrial DNA of Siniperca obscura from the Lijiang River. The size of the complete mitochondrial genome is 16,492 bp. The organization of the mitochondrial contained 37 genes (13 protein-coding genes, 2 ribosomal RNA and 22 transfer RNAs) and a major non-coding control region as well as those reported sinipercid fishes. Among the 13 protein-coding genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Siniperca knerii is also an economically important species to fisheries and aquaculture in southern China (Luo et al 2011). A few studies have employed microsatellite markers, mitochondrial genomes or exon-capture data to study population genetics or to infer the phylogenetic position of S. knerii (Chen et al 2014;Song et al 2017;Tian et al 2017), but no genome sequence is available for it or for any species of the Sinipercidae. Determining the genome sequence of S. knerii would provide a fundamental dataset for better examining its genetic variation and population history.…”
mentioning
confidence: 99%
“…Siniperca knerii is also an economically important species to fisheries and aquaculture in southern China (Luo et al 2011). A few studies have employed microsatellite markers, mitochondrial genomes or exon-capture data to study population genetics or to infer the phylogenetic position of S. knerii (Chen et al 2014;Song et al 2017;Tian et al 2017), but no genome sequence is available for it or for any species of the Sinipercidae. Determining the genome sequence of S. knerii would provide a fundamental dataset for better examining its genetic variation and population history.…”
mentioning
confidence: 99%
“…We refered previous mitogenome paper about Centrarchiformes (Broughton & Reneau, 2006;Chen et al, 2012Chen et al, , 2013Gan et al, 2014;Lavoué et al, 2014;Li et al, 2012Li et al, , 2013Liu et al, 2015;Lv et al, 2014;Miya et al, 2001Miya et al, , 2013Mukai & Sato, 2009;Oh et al, 2007;Prosdocimi et al, 2012;Setiamarga et al, 2008;Yagishita et al, 2009;Yamanoue et al, 2007). Phylogenetic analysis based on the mitogenome sequences using the neighbor-joining method showed that the C. herzi was closely related to C. kawamebari (Figure 1).…”
mentioning
confidence: 86%